Permanent haemichorea associated with transient hyperglycemia. (7th October 2011) - Slabu, Hannah; Savedia-Cayabyab, Sheila; Senior, Peter; Arnason, Terra
Abstract : Hyperglycemia is associated with several common neurological syndromes. Chorea, however, is a rare association that has only been documented in the literature recently. The triad of chorea, non-ketotic hyperglycemia and a high signal basal ganglia lesion on the T1 weighted brain MRI (C-H-BG) is considered to be a unique syndrome. C-H-BG refers to the onset of chorea during or shortly after (days to weeks) an episode of non-ketotic hyperglycemia. There is usually a high signal lesion in the basal ganglia on T1 weighted brain MRI that corresponds to the location of the chorea. Most case reports of C-H-BG have been described in Asians. C-H-BG is considered to be a benign condition in which the clinical and MRI signs resolve quickly upon correction of blood glucose levels. Here, the authors describe a case of C-H-BG in a middle aged Caucasian in whom the chorea did not resolve with improved glycemic control.